Gender and political violence in local governments in the Central Mexican Altiplano - Sam Bautista, María Magdalena (2016)
In Mexico they are still few studies describing in detail the political violence against women. The aim of this paper is to describe the political violence that have faced síndicas in a State of Central Mexican Altiplano after his rise to office in January 2014. It should be noted that before parity was approved nationally in the selection Candidate / os to elected office, such a mechanism was approved for the election of municipal authorities in Tlaxcala. The agreement by the local election authority that resulted in the 2014-2016 triennium, women were elected in almost all of the receiverships. Of the 60 receiverships in the state, 56 of them were represented by women and 5 men, that is, 91% of this elected office. This circumstance led to changes in the power relationships inside and outside the hall that led to conflicts between the mayor and the ombudswoman, which in several cases were characterized, as noted by the Association of Councillors of Bolivia (ACOBOL) by aggressive behaviors caused physical, psychological or sexual harm against a woman in the exercise of political representation, to prevent and restrict the exercise of his office or induce her to make decisions against its will, its principles and the law. This research describes the strategies followed by the Syndic of Tlaxcala to deal with such behavior. The reflection is done from a gender perspective, ie considering the roles assigned to women generate discrimination and inequalities, which result in differential access to resources, and therefore power. This work was based on several interviews with actors / as relevant (president / is acting municipal and / or were, síndicas, among other) allowing learn about their views, experiences and strategies. I also used the hemerographic review to document the characteristics of the conflict. The findings point to visualize the consequences of questioning the way in which power is exercised in local government, the results of the absence of operational structures for the operation of the law and the need for equal numbers include women in order to build from local democracy.